Travelling languages: toward a geolinguistic imagination. - Mary Louise Pratt (Nepan editor, 2013)
In a close dialogue with questions related to the understanding of linguistic dimensions which are featured around the planetary, social, ecological, economic, political, and imaginary realignments driven by contemporary globalization, this article is focused on the role and importance of language in terms of defining and even determining the processes and transformations wrought by this globalization. It especially takes into account the need to put the language in the center of this debate, as an important category of analysis for thinking about the dynamics of the ongoing transformations.